Pemanfaatan Media Bimbingan dan Konseling di Sekolah Menengah Kejuruan Muhammadiyah se-Kota Yogyakarta - Prasetiawan, Hardi; Alhadi, Said (Jurnal Kajian Bimbingan dan Konseling, 2018)
The particular study aimed to know the utilization of media in guidance and counseling service provided by school counselor. Quantitative approach was used in the study. The research instrument was questionnaire with five alternative answers, such: very often; often; rare; sometime; and never. The result of the study showed the use of media in guidance and counseling service by school counselor ranging from visual media, electronic media; audio visual media; computer media.